A MULTI-STEP APPROACH FOR ANALYZING THE NUMBER OF POLYMER INJECTION MOLDING GATE SPOTS AND THEIR POSITION IN T-RTM TECHNOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of this study is to present a multi-step approach for building a virtual analysis supporting the determination of the number and position of the injection molding gate spots in Resin Transfer Molding (RTM) and the relatively new Thermoplastic Resin Transfer Molding (T-RTM) technologies. The methodology provides an opportunity to determine the behavior of the fluid flow based on the location of the inlets, as well as potential problems and defects.